Pemilihan Supplier Urea Menggunakan Metode Analytic Network Process : (Studi Kasus di PT. Delta Setia Sandang Asli Tekstil 1) - Anindya Manggar Iwarani; Yunita Primasanti; Bekti Nugrahadi (Asosiasi Riset Ilmu Teknik Indonesia, 2025)
Supplier selection is a strategic element in supply chain management to ensure operational efficiency and business sustainability. This study aims to determine the best urea supplier for PT DSSA 1, a textile company specializing in dyeing and finishing processes, using the Analytic Network Process (ANP) method. This method was chosen for its ability to systematically analyze interdependencies among criteria, leading to more accurate and comprehensive decision-making. Data were collected through direct observation, in-depth interviews with internal company sources, and relevant literature reviews. The analysis was based on five main criteria: quality, price, service, delivery, and flexibility, each further broken down into sub-criteria. The results indicate that quality is the most critical criterion, with the highest weight of 23.19%, followed by price, service, and delivery, each with relatively balanced weights of 19.93%. Flexibility, although ranked last with a weight of 17.01%, remains relevant, especially for urgent orders. Based on the analysis, Supplier A was identified as the best choice with the highest overall weight, followed by Supplier B and Supplier C. This study provides practical contributions by offering strategic recommendations for PT DSSA 1 in selecting suppliers that support production efficiency and business sustainability. The study is limited in the scope of criteria and the number of suppliers analyzed. Future research is recommended to explore more variables, expand the sample size, and consider the implementation of digital technologies to optimize the supply chain.